The Influence of Scratch-Assisted Problem Based Learning (PBL) Model on Improving Elementary School Students' Mathematical Understanding Ability - Fauziah, Neneng Dwi; Rahayu, Puji; Putri, Hafiziani Eka (MID Publisher International, 2024)
This research is motivated by the low level of mathematical understanding among elementary school students. Mathematical understanding is crucial for students as it helps them interpret and solve both mathematical problems and everyday issues. The purpose of this study is to investigate the influence and effectiveness of the Problem-Based Learning (PBL) model, assisted by Scratch, on improving the mathematical understanding of elementary school students. The research method employed is a quasi-experiment using the Non-Equivalent Control Group Design. The sample consisted of 40 fifth-grade students from a state elementary school in a district of Purwakarta, with 20 students in class VA and 20 students in class VB. Class VA served as the experimental group, using the Problem-Based Learning (PBL) model assisted by Scratch, while class VB used conventional teaching methods. The results indicate that the PBL model, when assisted by Scratch, improved students mathematical understanding by 33.3%. Additionally, students who learned with the PBL model assisted by Scratch demonstrated better mathematical understanding compared to those who learned using conventional methods. Therefore, the PBL model can be considered an effective alternative for enhancing mathematical understanding skills.